Insights into the Quorum-Sensing Activity in Aeromonas hydrophila Strain M013 as Revealed by Whole-Genome Sequencing - Tan, Wen Si; Yin, Wai Fong; Chan, Kok Gan (American Society for Microbiology, 2015)
Aeromonas hydrophila species can be found in warm climates and can survive in different environments. They possess the ability to communicate within their populations, which is known as quorum sensing. In this work, we present the draft genome sequence of A. hydrophila M013, a bacterium isolated from a Malaysian tropical rainforest waterfall.